Hetero-polyionic hydrogels enable dendrites-free aqueous Zn-I₂ batteries with fast kinetics - Yang, Jin-Lin (2023)
Rechargeable aqueous Zn-I2 batteries (ZIB) are regarded as a promising energy storage candidate. However, soluble polyiodide shuttling and rampant Zn dendrite growth hamper its commercial implementation. Herein, a hetero-polyionic hydrogel is designed as the electrolyte for ZIBs. On the cathode side, iodophilic polycationic hydrogel (PCH) effectively alleviates the shuttle effect and facilitates the redox kinetics of iodine species. Meanwhile, polyanionic hydrogel (PAH) toward Zn metal anode uniformizes Zn2+ flux and prevents surface corrosion by electrostatic repulsion of polyiodides. Consequently, the Zn symmetric cells with PAH electrolyte demonstrate remarkable cycling stability over 3000 h at 1 mA cm-2 (1 mAh cm-2 ) and 800 h at 10 mA cm-2 (5 mAh cm-2 ). Moreover, the Zn-I2 full cells with PAH-PCH hetero-polyionic hydrogel electrolyte deliver a low-capacity decay of 0.008 ‰ per cycle during 18 000 cycles at 8 C. This work sheds light on hydrogel electrolytes design for long-life conversion-type aqueous batteries.